A grid platform for the european civil protection e-Infrastructure: the forest fires use scenario - Mazzetti, Paolo (2008)
During the full cycle of the emergency management, Civil Protection operative procedures involve many actors belonging to several institutions (civil protection agencies, public administrations, research centers, etc.) playing different roles (decision-makers, data and service providers, emergency squads, etc.). In this context the sharing of information is a vital requirement to make correct and effective decisions. Therefore a European-wide technological infrastructure providing a distributed and coordinated access to different kinds of resources (data, information, services, expertise, etc.) could enhance existing Civil Protection applications and even enable new ones. Such European Civil Protection e-Infrastructure should be designed and implemented taking into account the specific requirements of Civil Protection applications and the state-of-the-art in the scientific and technological disciplines which could make the emergency management more effective. In the last years Grid technologies have reached a mature state providing a platform for secure and coordinated resource sharing between the participants in the so-called Virtual Organizations. Moreover the Earth and Space Sciences Informatics provide the conceptual tools for modelling the geospatial information shared in Civil Protection applications during its entire lifecycle. Therefore a European Civil Protection e-infrastructure could be based on a Grid platform enhanced with Earth Sciences specific services. However Civil Protection applications have specific requirements that make them different from typical Earth System Sciences research applications. For example they often require Real-Time or Near-Real-Time support, privileging time-of-response instead of accuracy. Therefore a set of high-level services specifically tailored for such applications must be built on top of the Grid platform. As a result of a requirement analysis, the FP6 project CYCLOPS has proposed an architectural framework for the future European Civil Protection e-Infrastructure. In this architecture a layer of high-level services tailored to Civil Protection applications is built on top of the EGEE Grid middleware. In particular a set of geospatial services accessible through a standard interface and enabled to make use of Grid processing and storage capabilities, is provided. These services enable the sharing of geospatial information even with external Spatial Data Infrastructures, a fundamental requirement for Civil Protection application. Such architectural approach has been tested implementing a prototype of a grid-enabled RISICO, the application for wild fire risk assessment used by the Italian Civil Protection. The prototype makes use of a set of standard geospatial services implemented on top of the EGEE gLite Grid middleware. The prototyping activity demonstrated that the proposed architecture could help to to reach two important objectives. First of all, Civil Protection applications can gain great benefit from the underlying Grid infrastructure. Distributed processing reduces computation time allowing to provide more valuable products to decision-makers (e.g. high resolution maps in the RISICO applications). Moreover, the adoption of a standard geospatial layer makes Civil Protection applications more interoperable, allowing to access different data providers, and publishing output data for further processing. Anyway several issues are still open, both conceptual (e.g. semantic description of the information from data providers, data policy representation, etc.) and technological. Therefore more investigation is needed to implement this promising approach, in a real and effective infrastructure.